Hoffelijkheden. - Kenis, Jan (Hasselt : Begijnhof Centrum voor Kunsten, 1994)
Minnen, Raymond ; Caelen, Leon ; Frederickx, Henri ; Broodthaers, Marcel ; Panamarenko ; Geys, Jef ; Raveel, Roger ; Daems, Walter ; Charlier, Jacques ; Delvoye, Wim ; Bijl, Guillaume ; Van Caeckenbergh, Patrick ; Mc Kenna, Stephen
Hoffelijkheden, Begijnhof Centrum voor Kunsten, Hasselt, 1994
boek